Care transitions as street-level work: Providers' perspectives on the dilemmas and discretions of older people's transitions across acute, sub-acute and primary care. Issue 3 (3rd July 2017) - Foster, Michele; Harvey, Desley; Quigley, Rachel; Strivens, Edward
Abstract : Purpose: Quality care transitions of older people across acute, sub-acute and primary care are critical to safety and cost, which is the reason interventions to improve practice are a priority. Yet, given the complexity of providers and services involved it is often difficult to know the types of tensions that arise in day-to-day transition work or how front-line workers will respond. To that end, this innovative study differs from the largely descriptive studies by conceptualising care transitions as street-level work in order to capture how transition practice takes shape within the complexities and dynamics of the local setting. The paper aims to discuss these issues. Design/methodology/approach: Data were collected from 23 hospital health professionals and community service providers across primary, sub-acute and acute care through focus groups. A thematic analysis and interrogation of themes using street-level concepts derived three key themes. Findings: The themes of risk logics and dilemmas of fragmentation make explicit both the local constraints and opportunities of care transitions and how these intersect to engender a particular logic of practice. By revealing the various discretionary tactics adopted by front-line providers, the third theme simultaneously highlights how discretionary spaces might represent both possibilities and problematics for balancing organisational and patient needs. Originality/value: The study contributes to the knowledge of street-level work in health settings and specifically, the nature of transition work. Importantly, it benefits policy and practice by uncovering mechanisms that could facilitate and impede quality transitions in discrete settings.